A cultural analysis of the book "A Warm Winter" - Gurbet, Cagla (Technium Education and Humanities, 2023)
Children's books are an important tool that enables the child to communicate with the world he lives in through written and visual ways. Since learning starts at an early age, it is essential for the child to read books suitable for his/her age and purpose in order to take part in the adult world as a qualified individual who has acquired the habit of reading and to reach cognitive adulthood. As in all types of literature, cultural differences can be seen in the translations of children's literature. These differences can be encountered visually or textually. The aim of the study is the linguistic/visual reflections of the social and cultural elements given in the work to be examined and which translation strategies are used to transfer them to the target language. Within the scope of the study, first of all, the external and internal features of children's books will be mentioned, and then the Turkish edition of Feridun Oral's "Nobody Will Be Cold This Winter" by Yapı Kredi Publishing in February 2020 and the English translation of Melis Seyhun Çalışlar will be published by Yapı Kredi Publishing in October. The 2019 edition will be examined within the scope of Vermeer's Skopos theory.